1999
DOI: 10.1016/s0378-1127(98)00365-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of seven silvicultural treatments on terrestrial salamanders

Abstract: We compared the relative abundance of terrestrial salamanders before and after application of seven regeneration treatments in a low-elevation, southern Appalachian hardwood forest in southwest Virginia. Treatments included understory removal, group selection, two shelterwoods, leave-tree, clearcut, and a control. Salamander relative abundance was signi®cantly lower after harvest on the group selection (p0.005), shelterwoods (p0.007 and p0.015), leave-tree (p0.001), and clearcut treatments (p0.001). There was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
105
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(115 citation statements)
references
References 16 publications
(14 reference statements)
8
105
2
Order By: Relevance
“…In the southeastern United Slates, species diversity of wodland salamanders (family: Plethodontidae) reaches its zenith in the southern Appalachians (Martof et al, 1980, Wilson, 1995. Accordingly, recent attention has fwused on the negative impact of clearcutting on woodland salamanders within the region (Ash, 1988(Ash, , 1997Petrmka et al,, 1993Petrmka et al,, , 1994Harpole and Haas, 1999). In the s h o~-t e m , clearcutting in the southern Appalachians prduces habitat conditions unfavorable for salamanders by increasing forest floor temprtllures (Johnson et at., 1985) and reducing leaf litter depth and microsite moisture (Ash, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In the southeastern United Slates, species diversity of wodland salamanders (family: Plethodontidae) reaches its zenith in the southern Appalachians (Martof et al, 1980, Wilson, 1995. Accordingly, recent attention has fwused on the negative impact of clearcutting on woodland salamanders within the region (Ash, 1988(Ash, , 1997Petrmka et al,, 1993Petrmka et al,, , 1994Harpole and Haas, 1999). In the s h o~-t e m , clearcutting in the southern Appalachians prduces habitat conditions unfavorable for salamanders by increasing forest floor temprtllures (Johnson et at., 1985) and reducing leaf litter depth and microsite moisture (Ash, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Messere and Ducey (1998) reported that low intensity selective cutting (gaps from 22 to 94 m 2 ) did not affect red-backed salamander abundance 1 yr after cutting. Harpole and Haas (1999), however, noted that salamanders were less abundant in selective cuts compared with control forests 1 to 3 yr after cutting. Residual BA in their study (selective cutting: 4-7 and 12-15 m 2 , scattered seed tree cutting: 3-4 m 2 ) were much lower than the residual BA at Duchesnay after 6 and 8 yr (~ 21 m 2 ).…”
Section: Salamandersmentioning
confidence: 88%
“…Despite their importance, few studies have investigated the impact of forest management on soil arthropods in northeastern United States and Canada (Jennings et al 1984;Bird and Chatarpaul 1986;Duchesne et al 1999) in comparison to salamanders (Caudata) (c.f. deMaynadier et Hunter 1995Hunter , 1998Messere and Ducey 1998;Satter and Reichenbach 1998;Harpole and Haas 1999) and shrews (Soricidae) (c.f. Kirkland 1990;Mitchell et al 1997;Menzel et al 1999).…”
mentioning
confidence: 99%
“…In low-elevation forests of Virginia, relative abundance of salamanders was lower after group selection, shelterwoods, leave-tree, and clear-cut harvest treatments, but there was no significant difference in relative abundance between control and understory removal treatments [123]. Of several oak regeneration options, Homyack and Haas [124] indicate that group selection harvest facilitates the quickest population recovery for salamanders.…”
Section: Timber Harvestmentioning
confidence: 93%